2023
DOI: 10.1177/00472875221146784
|View full text |Cite
|
Sign up to set email alerts
|

Animosity and Tourism: Resident Perspectives

Abstract: Despite the growing interest that scholars have paid to animosity in tourism settings, pertinent research draws mostly from tourist perspectives to examine the effects of animosity on travel-related decision-making. The aim of this study is to explore the animosity perceptions of residents against Russian tourists who, following the Russia-Ukraine conflict and the sanctions imposed on Russia, are likely to experience intense animosity when traveling abroad. The study draws from interviews with residents based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Scholars contended that consumer animosity arose from hatred or social, economic or political competition (Ali, 2021; Leonidou et al , 2019; Suhud and Allan, 2021). There is a dearth of research on consumer animosity in a country-specific context (Farmaki, 2023; Koh, 2014), which we studied, and our findings confirm the connection between consumers’ animosity toward Russian brands and their negative attitude. This supports the findings of Han et al (2021), who found that consumer animosity has a negative effect on brand attitude.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Scholars contended that consumer animosity arose from hatred or social, economic or political competition (Ali, 2021; Leonidou et al , 2019; Suhud and Allan, 2021). There is a dearth of research on consumer animosity in a country-specific context (Farmaki, 2023; Koh, 2014), which we studied, and our findings confirm the connection between consumers’ animosity toward Russian brands and their negative attitude. This supports the findings of Han et al (2021), who found that consumer animosity has a negative effect on brand attitude.…”
Section: Discussionsupporting
confidence: 80%
“…This study contributes to the theory of international business in the following ways: First, this study expands on recent work that examined the residents perceived animosity toward Russian tourists (Farmaki, 2023). Although a few studies examined the effects of animosity on product judgment and attitude toward products (Westjohn et al , 2021; Zdravkovic et al , 2021), our findings confirmed that European customers’ have animosity toward Russian brands due to anger and hate, which resulted in the Russia–Ukraine war.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Unfavorable perceptions and media portrayal of a country's political situation or security threats can have a long-lasting impact on its image. Rebuilding trust and reestablishing a positive reputation may take considerable effort and time, further affecting tourism and economic growth (Avraham, 2015;Farmaki, 2023).…”
Section: Introductionmentioning
confidence: 99%